All-solid-state electrolyte and preparation method and application thereof

CN120473658BActive Publication Date: 2026-10-27BEIJING INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510392607.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-27
Estimated Expiration
2045-03-31

AI Technical Summary

Technical Problem

[0002]结构储能复合材料以及使用多孔树脂膜作为隔膜的纽扣电池等常规储能材料只能使用液态电解质作为传输介质,这严重限制了电解质的可选范围,和各项功能,

Benefits of technology

[0041]与现有技术相比,本发明的有益效果在于:本发明所提供的全固态电解质可以作为传统液态电解质的潜在替代品,其优势在于具有更好的安全性、稳定性、更广泛的工作温度范围、更高的能量密度、更好的循环性能及有效抑制锂枝晶的生长。该种全固态电解质可显著提高电池的安全性(因为其无溶剂存在)和稳定性,其可应用于固态电解质电池的安装及应用,在能源存储、传感器技术、微纳米电子器件、汽车制造、微电子产品等多个领域具有广泛的应用前景,本发明在全固态电解质孔洞结构中引入Li离子固态电解质溶液(Li离子固态电解质溶液以溶液的形式浸入多孔树脂的孔洞中,然后通过挥发溶剂的形式在多孔树脂的孔洞中进行沉积并填充),将多孔树脂转变为多孔树脂-全固态电解质的实心结构有利于提升材料整体力学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120473658B_ABST
    Figure CN120473658B_ABST
Patent Text Reader

Abstract

The application discloses a kind of all-solid-state electrolyte and its preparation method and application, the preparation method of the all-solid-state electrolyte is porous resin preparation piece is soaked in Li ion solid electrolyte solution, after solvent volatilization is complete, all-solid-state electrolyte is obtained.The application introduces Li ion solid electrolyte solution (Li ion solid electrolyte solution is immersed in the form of solution in the hole of porous resin, then is deposited and filled in the hole of porous resin by the form of volatilizing solvent) in all-solid-state electrolyte hole structure, porous resin is changed into the solid structure of porous resin-all-solid-state electrolyte, this is advantageous to promote the overall mechanical properties of material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrolyte technology, and particularly relates to an all-solid-state electrolyte, its preparation method and application. Background Technology

[0002] Conventional energy storage materials, such as structural energy storage composites and button batteries using porous resin membranes as separators, can only use liquid electrolytes as the transport medium. This severely limits the range of electrolyte options and their various functions. Furthermore, if structural energy storage composites are prepared using a porous resin plus liquid electrolyte method, the resulting void structure leads to deviations in overall mechanical properties. Summary of the Invention

[0003] To address the aforementioned technical problems, one objective of this invention is to provide a simple and high-performance method for preparing an all-solid-state electrolyte.

[0004] To achieve the above objectives, the technical solution of the present invention is as follows: a method for preparing an all-solid electrolyte, wherein a porous resin component is immersed in a Li-ion solid electrolyte solution, and the all-solid electrolyte is obtained after the solvent has evaporated.

[0005] The method for preparing the porous resin part described in the above technical solution includes the following steps:

[0006] Step 1a: Mix the resin matrix with the pore-forming agent to form a homogeneous mixed solution.

[0007] Step 2a: Add the curing agent to the first mixed solution, mix well to obtain the second mixed solution, and then perform molding treatment on the second mixed solution to obtain the blank;

[0008] Step 3a: Soak the preform in deionized water, then remove and dry it to obtain the porous resin part.

[0009] The porous resin parts described in the above technical solution must meet at least one of the following conditions during preparation:

[0010] A1: The mass ratio of resin matrix to pore-forming agent in step 1a is 1:1-4 (which can be any ratio of 1:1, 1:2, 1:3, 1:4 or any range between any two ratios);

[0011] B1: In step 1a, the mixing temperature of the resin matrix and the pore-forming agent is 25-60℃ (which can be any value or any range between any two of 25℃, 30℃, 35℃, 40℃, 45℃, 50℃, 55℃ and 60℃), and the stirring time is 0.2-0.5h (which can be any value or any range between any two of 0.2h, 0.25h, 0.3h, 0.35h, 0.4h, 0.45h and 0.5h).

[0012] C1: The mass ratio of curing agent to resin matrix in step 2a is 2-5:10 (which can be any ratio among 1:5, 3:10, 2:5, and 1:2, or any range between any two ratios);

[0013] D1: The mixing time in step 2a is 20-60 min (which can be any value or a range between any two values ​​from 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min and 60 min);

[0014] E1: In step 2a, the molding process involves adding the mixed solution II into a closed mold with a thickness of 50-300 μm (any value or the range between any two of the following: 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, 260 μm, 270 μm, 280 μm, 290 μm, and 300 μm) for curing. The resulting green body has a curing time of 2-6 hours (which can be any value or any range between any two of the following: 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, and 6 hours), and a curing temperature of 100-200℃ (which can be any value or any range between any two of the following: 100℃, 105℃, 110℃, 115℃, 120℃, 125℃, 130℃, 135℃, 140℃, 145℃, 150℃, 155℃, 160℃, 165℃, 170℃, 175℃, 180℃, 185℃, 190℃, 195℃, and 200℃).

[0015] F1: The soaking time in step 3a is 24-48 hours (it can be any value or a range between any two of the following: 24h, 25h, 26h, 27h, 28h, 29h, 30h, 31h, 32h, 33h, 34h, 35h, 36h, 37h, 38h, 39h, 40h, 41h, 42h, 43h, 44h, 45h, 46h, 47h, and 48h), and the drying temperature is 30-80℃ (it can be 30℃). The temperature range is 35℃, 40℃, 45℃, 55℃, 60℃, 65℃, 70℃, 75℃ and 80℃ (any value or a range between any two values), and the drying time is 6-24h (any value or a range between any two values ​​among 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h and 24h).

[0016] The resin matrix described in the above technical solution is at least one of bisphenol A type epoxy resin, bisphenol F type epoxy resin, acrylic resin and 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane;

[0017] The curing agent is an amine-based curing agent;

[0018] The pore-forming agent is at least one of polyethylene glycol, glucose, propylene carbonate, and N,N-dimethylformamide.

[0019] The bisphenol A type epoxy resin mentioned in the above technical solution is E51 type and / or E44 type bisphenol A type epoxy resin;

[0020] The bisphenol F type epoxy resin is Epikote 862 liquid bisphenol F type epoxy resin;

[0021] The acrylic resin is JONCRYL 678 type solid waterborne acrylic resin;

[0022] The amine curing agent is at least one of D-400 curing agent, PACM curing agent, DDM curing agent, and TETA curing agent.

[0023] In the above technical solution, the porous resin component is dried while being immersed in a Li-ion solid electrolyte solution to accelerate volatilization. The drying temperature is 40-70℃ (which can be any value or any two of 40℃, 45℃, 55℃, 60℃, 65℃ and 70℃), and the drying time is more than 24 hours (preferably 24-48 hours, which can be any value or any two of 24h, 25h, 26h, 27h, 28h, 29h, 30h, 31h, 32h, 33h, 34h, 35h, 36h, 37h, 38h, 39h, 40h, 41h, 42h, 43h, 44h, 45h, 46h, 47h and 48h).

[0024] The preparation method of the Li ion solid electrolyte solution described in the above technical solution includes the following steps:

[0025] Step 1b: Activate oxaloyl chloride by adding it to N,N-dimethylformamide containing dry acetonitrile;

[0026] Step 2b: Add the activated oxaloyl chloride to sodium 4-styrenesulfonate to obtain 4-styrenesulfonyl chloride;

[0027] Step 3b: Mix the obtained 4-styrenesulfonyl chloride with an equimolar amount of 4-(trifluoromethoxy)benzenesulfonamide to obtain a mixed solution. Concentrate the mixed solution to 1 / 10-1 / 5 of the original volume to obtain a brown substance. Then dissolve the brown substance in dichloromethane to obtain a mixed solution.

[0028] Step 4b: Wash the mixture with NaHCO3 aqueous solution and hydrochloric acid solution respectively, then evaporate to remove the solvent. Dry the concentrated solution to obtain a dry solid, and weigh the obtained substance.

[0029] Step 5b: Dissolve the dried solid obtained above in LiOH aqueous solution, and after stirring the reaction thoroughly, obtain lithium 4-styrenesulfonyl (phenylsulfonyl)imide;

[0030] Step 6b: Add lithium 4-styrenesulfonyl (phenylsulfonyl)imide to THF solution, centrifuge and dry to obtain solid Li salt electrolyte;

[0031] Step 7b: Dissolve the Li salt electrolyte in methyl sulfoxide and add PVDF-HFP crosslinking blend to form a Li ion solid electrolyte solution.

[0032] The porous resin parts described in the above technical solution must meet at least one of the following conditions during preparation:

[0033] A2: In step 1b, the molar ratio of oxaloyl chloride to N,N-dimethylformamide is 20-30:1;

[0034] B2: In step 2b, the molar ratio of oxaloyl chloride to sodium 4-styrenesulfonate is 0.5-0.5:1;

[0035] C2: The concentration of NaHCO3 aqueous solution in step 4b is 3-5 wt%, and its amount is 2-4 times the volume of the mixed solution;

[0036] D2: The concentration of the hydrochloric acid solution in step 4b is 0.8-1.2M, and the amount used is 3-5 times that of mixture four;

[0037] E2: Step 5b involves dissolving the dried solid obtained above in 0.9-1.3 times the equivalent concentration of 0.4-0.6M LiOH aqueous solution at a molar ratio;

[0038] F2: In step 7b, the mass ratio of Li salt electrolyte, methyl sulfoxide and PVDF-HFP is 1:4-4.5:0.2-0.7.

[0039] The second objective of this invention is to provide a high-performance all-solid electrolyte prepared by the method described above.

[0040] The third objective of this invention is to provide an application of the all-solid-state electrolyte described above as a separator or structural energy storage composite material in a coin cell.

[0041] Compared with existing technologies, the beneficial effects of this invention are as follows: The all-solid-state electrolyte provided by this invention can serve as a potential alternative to traditional liquid electrolytes. Its advantages include better safety, stability, a wider operating temperature range, higher energy density, better cycle performance, and effective suppression of lithium dendrite growth. This all-solid-state electrolyte can significantly improve battery safety (due to the absence of solvents) and stability. It can be applied to the installation and use of solid-state electrolyte batteries and has broad application prospects in energy storage, sensor technology, micro / nanoelectronic devices, automotive manufacturing, microelectronic products, and many other fields. This invention introduces a Li-ion solid electrolyte solution into the porous structure of the all-solid-state electrolyte (the Li-ion solid electrolyte solution is immersed in the pores of the porous resin in solution form, and then deposited and filled in the pores of the porous resin through solvent evaporation), transforming the porous resin into a solid structure of porous resin-all-solid-state electrolyte, which is beneficial to improving the overall mechanical properties of the material. Attached Figure Description

[0042] Figure 1 This is a schematic diagram of the sheet-like sample in an embodiment of the present invention. Detailed Implementation

[0043] The principles and features of the present invention are described below with reference to the accompanying drawings. The examples given are only for explaining the present invention and are not intended to limit the scope of the present invention.

[0044] Example 1

[0045] In this embodiment, the mass ratio of resin matrix to pore-forming agent in the preparation of porous resin is 1:3, the mixing temperature of resin matrix and pore-forming agent is 25°C, and the stirring time is 0.2h; and the mass ratio of curing agent to resin matrix is ​​1:2, the stirring time during mixing is 20min. The molding process involves adding the mixed solution to a closed mold for curing to obtain the green body, wherein the curing time is 2h, and the curing temperature is 180°C; in step 3, the soaking time is 24h, the drying temperature is 30°C, and the drying time is 24h. The resin matrix is ​​E44 type bisphenol A type epoxy resin, the curing agent is PACM curing agent, and the pore-forming agent is polyethylene glycol.

[0046] Example 2

[0047] Similar to Example 1, the difference lies in that, during the preparation of the porous resin, the mass ratio of the resin matrix to the pore-forming agent is 1:2, the mixing temperature of the resin matrix and the pore-forming agent is 40°C, and the stirring time is 0.3h; the mass ratio of the curing agent to the resin matrix is ​​3:10, the stirring time during mixing is 30min, and the molding process involves adding the mixed solution 2 into a closed mold for curing to obtain the green body, wherein the curing time is 3h, and the curing temperature is 150°C; in step 3, the soaking time is 30h, the drying temperature is 40°C, and the drying time is 10h, wherein the resin matrix is ​​E51 type bisphenol A type epoxy resin, the curing agent is PACM curing agent, and the pore-forming agent is glucose.

[0048] Example 3

[0049] Similar to Example 1, the difference lies in that, during the preparation of the porous resin, the mass ratio of the resin matrix to the pore-forming agent is 1:3, the mixing temperature of the resin matrix and the pore-forming agent is 50°C, and the stirring time is 0.4h; in step 2, the mass ratio of the curing agent to the resin matrix is ​​2:5, the stirring time during mixing is 40min, and the molding process involves adding the mixed solution to a closed mold for curing to obtain the green body, wherein the curing time is 8h, and the curing temperature is 100°C; in step 3, the soaking time is 35h, the drying temperature is 50°C, and the drying time is 15h, wherein the resin matrix is ​​Epitome 862 liquid bisphenol F type epoxy resin, the curing agent is DDM curing agent, and the pore-forming agent is propylene carbonate.

[0050] Example 4

[0051] Similar to Example 1, the difference lies in that, during the preparation of the porous resin, the mass ratio of the resin matrix to the pore-forming agent is 1:4, the mixing temperature of the resin matrix and the pore-forming agent is 60°C, and the stirring time is 0.5h; in step 2, the mass ratio of the curing agent to the resin matrix is ​​1:2, the stirring time during mixing is 60min, and the molding process involves adding the mixed solution 2 into a closed mold for curing to obtain the green body, wherein the curing time is 6h, and the curing temperature is 180°C; in step 3, the soaking time is 48h, the drying temperature is 80°C, and the drying time is 24h, wherein the resin matrix is ​​JONCRYL 678 type solid waterborne acrylic resin, the curing agent is TETA curing agent, and the pore-forming agent is N,N-dimethylformamide.

[0052] Example 5

[0053] Preparation of Li-ion solid electrolyte solution

[0054] The preparation method of Li ion solid electrolyte solution includes the following steps:

[0055] Step 1: Activate by adding 25 mmol of oxaloyl chloride to 1 mmol of N,N-dimethylformamide containing dry acetonitrile;

[0056] Step 2: Add the activated oxaloyl chloride to 25 mmol of sodium 4-styrene sulfonate to obtain 4-styrene sulfonyl chloride;

[0057] Step 3: Mix the obtained 4-styrenesulfonyl chloride with an equimolar amount of 4-(trifluoromethoxy)benzenesulfonamide to obtain mixed solution three. Then, use a rotary evaporator to evaporate and concentrate the solution to 10 mL at 45 degrees Celsius to obtain a brown substance. Dissolve the substance in dichloromethane solution to obtain mixed solution four.

[0058] Step 4: Wash the above mixture with 4wt% NaHCO3 aqueous solution (80mL) and 1M hydrochloric acid (40mL), then remove the solvent using a rotary evaporator. Place the concentrated solution in a vacuum oven and heat it at 60℃ for 24h to obtain a dry solid. Weigh the obtained substance.

[0059] Step 5: The dried solid obtained above is reacted with 0.5 mL of iOH aqueous solution by molar ratio and stirred for 24 h to obtain lithium 4-styrenesulfonyl (phenylsulfonyl)imide;

[0060] Step 6: Add lithium 4-styrenesulfonyl (phenylsulfonyl)imide to THF solution, centrifuge and dry to obtain solid Li salt electrolyte;

[0061] Step 7: Dissolve the Li salt electrolyte in methyl sulfoxide and add PVDF-HFP crosslinked blend (mixed at a mass ratio of 1:4.26:0.5) to form a Li ion solid electrolyte solution.

[0062] Performance Test 1

[0063] Dumbbell-shaped films (narrow in the middle and wide at both ends) were prepared according to the preparation processes of Examples 1-4, namely Film 1, Film 2, Film 3 and Film 4 for later use;

[0064] Multiple films of film 1, film 2, film 3 and film 4 were immersed in the Li ion solid electrolyte solution prepared in Example 5 to prepare all-solid electrolytes, and all-solid electrolyte 1, all-solid electrolyte 2, all-solid electrolyte 3 and all-solid electrolyte 4 were obtained for later use.

[0065] According to the standard GB / T1040 for the determination of tensile properties of plastics, the LE5000 series electronic universal testing machine was used to test the above-prepared films 1, 2, 3, and 4, as well as all-solid electrolytes 1, 2, 3, and 4. The specific test method is as follows: The sample is placed in the testing machine fixture, ensuring that the clamping area is completely fixed and the clamping position is centered. The central axis of the sample is aligned with the loading axis to avoid eccentric force. The tensile rate is set as follows: the clamping head moving speed is 2 mm / min. The test sample is a dumbbell-shaped sheet structure, and its shape is as follows: Figure 1 As shown, the thickness is 2mm, and it is widened at both ends. The length of the widened part is b, the width is c, and the length of the effective middle section is a. Among them, a is about 30mm, b is about 20mm, c is about 10mm, and the width of the effective middle section is 3-5mm (5mm is preferred).

[0066] Meanwhile, the samples of all-solid-state electrolyte I, all-solid-state electrolyte II, all-solid-state electrolyte III, and all-solid-state electrolyte IV prepared above were used as the electrolyte portion of button batteries for electrical performance testing. Lithium iron phosphate was used as the positive electrode and graphite as the negative electrode. The main tests were for charge-discharge capacity, and the specific capacity (mAh / g) and the percentage decay after 100 cycles were calculated from the discharge capacity. Specific results are shown in Table 1.

[0067] Table 1 shows the performance test results of the thin film and all-solid-state electrolyte corresponding to Examples 1-4.

[0068] Thin film 1 15.01 - - Film 2 18.50 - - Film three 16.69 - - Thin film four 10.25 - - All-solid-state electrolyte 19.53 96.31 92.28% All-solid electrolyte II 22.60 56.29 81.02% All-solid-state electrolyte three 20.18 97.36 92.59% All-solid-state electrolyte four 14.45 97.07 92.31%

[0069] As shown in the table above, the mechanical properties of film 3 reach 16.69 MPa, while those of all-solid-state electrolyte 3 reach 20.18 MPa. The specific capacity reaches 97.36 mAh / g, and the percentage decay after 100 cycles is 92.59%. This indicates that film 3 maintains relatively good mechanical properties while retaining a high specific capacity, and the retention rate after 100 cycles is also good. Furthermore, the above series of experiments demonstrates that introducing an all-solid-state electrolyte into porous resin significantly improves the mechanical properties of the materials.

[0070] Note: Films 1-4 are made of pure resin and have no electrochemical properties, so their specific capacity and percentage decay over 100 cycles were not tested.

[0071] Performance Test 2

[0072] According to the porous resin preparation process of Examples 1-4 and with reference to the preparation process of structural energy storage composite materials, block-shaped porous resins were prepared respectively. The specific dimensions of the blocks were 250mm in length, 15mm in width, and 2mm in thickness. These blocks were designated as Block 1, Block 2, Block 3, and Block 4 for later use.

[0073] The general process for preparing structural energy storage composite materials is as follows:

[0074] Active material powders of lithium iron phosphate (positive electrode) and graphite (negative electrode), binder, and conductive agent were added sequentially to N-methylpyrrolidone solvent in a mass ratio of 8:1:1 to obtain a slurry, wherein the weight ratio of solvent to material was 2.6:1. The stirred slurry was coated onto carbon fiber at a thickness of 30-40 μm using a blade coating method. It was dried at 90°C until all solvent evaporated. Finally, it was cut to the required size and assembled into a laminated structure according to the form of positive electrode, separator, and negative electrode. The epoxy resin, curing agent, and pore-forming agent prepared in the above examples were mixed using a flow-guiding method. The liquid is introduced into the laminated structure (i.e., porous resin is introduced in situ), and cured using the corresponding curing process. The pore-forming agent is removed by soaking, and the mixture is dried. The structural energy storage composite material is then immersed in the solid electrolyte solution prepared in Example 5 and dried to obtain a structural energy storage composite material with an internal pore structure (the porous resin introduced in structural energy storage composite material one corresponds to that in Example 1, the porous resin introduced in structural energy storage composite material two corresponds to that in Example 2, the porous resin introduced in structural energy storage composite material three corresponds to that in Example 3, and the porous resin introduced in structural energy storage composite material four corresponds to that in Example 4).

[0075] Samples for electrical and mechanical performance testing were prepared according to the above process methods. The structural energy storage composite material sample for electrical performance testing was a 4×4cm cuboid structure. For mechanical performance testing, both the block containing porous resin but without solid electrolyte and the structural energy storage composite material containing porous resin and solid electrolyte were prepared according to the standard ASTM D3039 for tensile testing of composite materials. The tensile test samples were prepared using an LE5000 series electronic universal testing machine. The specific test methods were performed according to the standard.

[0076] The mechanical properties of block 1, block 2, block 3, block 4, structural energy storage composite material 1, structural energy storage composite material 2, structural energy storage composite material 3, and structural energy storage composite material 4 were also tested. The specific results are shown in Table 2.

[0077] Table 2 shows the performance test results of the bulk and structural energy storage composite materials corresponding to Examples 1-4.

[0078] Block 1 185.30 Block Two 211.25 Block Three 191.09 Block Four 130.57 Structural energy storage composite materials 216.30 Structural energy storage composite materials II 254.38 Structural energy storage composite materials 217.26 Structural energy storage composite materials IV 150.69

[0079] The electrochemical performance of each structural energy storage composite material was characterized using the Blue Electric system; the specific results are shown in Table 3.

[0080] Table 3 shows the performance test results of the structural energy storage composite materials corresponding to Examples 1-4.

[0081] Structural energy storage composite materials 98.64 76.07% Structural energy storage composite materials II 67.78 47.80% Structural energy storage composite materials 104.11 77.24% Structural energy storage composite materials IV 103.08 77.09%

[0082] As shown in the table above, the mechanical properties of bulk material 3 reach 191.09 MPa, and those of structural energy storage composite material 1 reach 254.38 MPa. Simultaneously, the specific capacity of the electrical test sample prepared using this method reaches 104.11 mAh / g, with a decay percentage of 77.24% after 100 cycles. This indicates that structural energy storage composite material 3 maintains good mechanical properties while also possessing excellent electrical properties. Furthermore, the above series of experiments demonstrates that introducing an all-solid-state electrolyte into the porous resin-structural energy storage composite material significantly improves the mechanical properties of the materials.

[0083] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any equivalent changes, modifications, and evolutions made to the above embodiments based on the essential technology of the present invention shall still fall within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing an all-solid-state electrolyte, characterized in that, The porous resin part is immersed in a Li-ion solid electrolyte solution, and the all-solid electrolyte is obtained after the solvent evaporates completely; The method for preparing the porous resin part includes the following steps: Step 1a: Mix the resin matrix with the pore-forming agent to form a homogeneous mixed solution. Step 2a: Add the curing agent to the first mixed solution, mix well to obtain the second mixed solution, and then perform molding treatment on the second mixed solution to obtain the blank; Step 3a: Immerse the preform in deionized water, then remove and dry it to obtain the porous resin part; The preparation method of the Li ion solid electrolyte solution includes the following steps: Step 1b: Activate oxaloyl chloride by adding it to N,N-dimethylformamide containing dry acetonitrile; Step 2b: Add the activated oxaloyl chloride to sodium 4-styrenesulfonate to obtain 4-styrenesulfonyl chloride; Step 3b: Mix the obtained 4-styrenesulfonyl chloride with an equimolar amount of 4-(trifluoromethoxy)benzenesulfonamide to obtain a mixed solution. Concentrate the mixed solution to 1 / 10-1 / 5 of the original volume to obtain a brown substance. Then dissolve the brown substance in dichloromethane to obtain a mixed solution. Step 4b: Wash the mixture with NaHCO3 aqueous solution and hydrochloric acid solution respectively, then evaporate to remove the solvent. Dry the concentrated solution to obtain a dry solid, and weigh the obtained substance. Step 5b: Dissolve the dried solid obtained above in LiOH aqueous solution, and after stirring the reaction thoroughly, obtain lithium 4-styrenesulfonyl(4-trifluoromethoxyphenylsulfonyl)imine; Step 6b: Add 4-styrenesulfonyl (4-trifluoromethoxyphenylsulfonyl)imine lithium salt to THF solution, centrifuge and dry to obtain solid Li salt electrolyte; Step 7b: Dissolve the Li salt electrolyte in methyl sulfoxide and add PVDF-HFP crosslinking blend to form a Li ion solid electrolyte solution.

2. The method for preparing the all-solid-state electrolyte according to claim 1, characterized in that, The porous resin part must meet at least one of the following conditions during its preparation: A1: The mass ratio of resin matrix to pore-forming agent in step 1a is 1:1-4; B1: In step 1a, the temperature for mixing the resin matrix and the pore-forming agent is 25-60℃, and the stirring time is 0.2-0.5h; C1: The mass ratio of curing agent to resin matrix in step 2a is 2-5:10; D1: The mixing time in step 2a is 20-60 minutes; E1: In step 2a, the molding process involves adding the mixed solution II into a closed mold for curing to obtain the blank. The curing time is 2-6 hours and the curing temperature is 100-180℃. F1: In step 3a, the soaking time is 24-48 hours, the drying temperature is 30-80℃, and the drying time is 6-24 hours.

3. The method for preparing the all-solid-state electrolyte according to claim 1, characterized in that, The resin matrix is ​​at least one of bisphenol A type epoxy resin, bisphenol F type epoxy resin, acrylic resin and 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane; The curing agent is an amine-based curing agent; The pore-forming agent is at least one of polyethylene glycol, glucose, propylene carbonate, and N,N-dimethylformamide.

4. The method for preparing the all-solid-state electrolyte according to claim 3, characterized in that, The bisphenol A type epoxy resin is E51 type and / or E44 type bisphenol A type epoxy resin; The bisphenol F epoxy resin is Epikote 862 liquid bisphenol F epoxy resin; The acrylic resin is JONCRYL 678 type solid waterborne acrylic resin; The amine curing agent is at least one of D-400 curing agent, PACM curing agent, DDM curing agent, and TETA curing agent.

5. The method for preparing an all-solid-state electrolyte according to claim 1, characterized in that, The porous resin component is dried while being immersed in a Li-ion solid electrolyte solution to accelerate volatilization. The drying temperature is 40-70℃ and the drying time is more than 24 hours.

6. The method for preparing the all-solid-state electrolyte according to claim 1, characterized in that, The porous resin part must meet at least one of the following conditions during its preparation: A2: In step 1b, the molar ratio of oxaloyl chloride to N,N-dimethylformamide is 20-30:1; B2: In step 2b, the molar ratio of oxaloyl chloride to sodium 4-styrenesulfonate is 0.5-0.5:1; C2: The concentration of NaHCO3 aqueous solution in step 4b is 3-5 wt%, and its amount is 2-4 times the volume of the mixed solution; D2: The concentration of the hydrochloric acid solution in step 4b is 0.8-1.2M, and the amount used is 3-5 times that of mixture four; E2: Step 5b involves dissolving the dried solid obtained above in 0.9-1.3 times the equivalent concentration of 0.4-0.6M LiOH aqueous solution at a molar ratio; F2: In step 7b, the mass ratio of Li salt electrolyte, methyl sulfoxide and PVDF-HFP is 1:4-4.5:0.2-0.

7.

7. An all-solid-state electrolyte, characterized in that, It is prepared by the preparation method described in any one of claims 1-6.

8. An application of the all-solid-state electrolyte as described in claim 7, characterized in that, The all-solid electrolyte is used as a separator in a coin cell or as a structural energy storage composite material.

Citation Information

Patent Citations

  • Preparation and application of single-ion conductive polymer electrolyte membrane

    CN110003399A

  • Elastomer epoxy resin-based all-solid-state electrolyte as well as preparation method and application thereof

    CN112421104A

  • High-mechanical porous structure electrolyte as well as preparation method and application thereof

    CN118645702A